(36 3/4" + 36 3/8" + 371/2" +z) /4 = 36 5/8"
This is the equation that you would get for the average. Now we just solve for z.
Following PEMDAS you have to mulitply the equation by 4 to get rid of the divide by 4 part.
4( (36 3/4" + 36 3/8" + 371/2" +z) /4 = 36 5/8)
Which does this
36 3/4" + 36 3/8" + 371/2" +z = 146 1/2"
Now you have to add and subtract to get "z" by itself.
36 3/4" + 36 3/8" + 371/2" = 110 5/8"
(110 5/8" + z = 146 1/2" ) -110 5/8"
z= 35 7/8", so the answer is b
Answer:
Now, 3x 2+x+5⩾0
This is because b² −4ac=1−4×5×3
=−59 (roots are imaginary)
3x²+x+5=(x−3)² =x²+9−6x and x−3⩾0
2x²+7x−4=0
2x²+8x−x−4=0
2x(x+4)−1(x+4)=0
(2x−1)(x+4)=0
x= 1/2 and−4 but x≥3
∴ No solution.
lol hehehe
<span>7s over 5t to the negative 3rd power 2 to the negative 3rd power times X to the 2nd power times Z to the negative 7th power 7s to the zero power times T to the negative 5th power over 2 to the negative 1st power times M to the 2nd power If you would please simplify these </span>
Answer: m
= 5/2
Step-by-step explanation: